Cyclist Reynolds number effects and drag crisis distribution. Issue 200 (May 2020) - Terra, W.; Sciacchitano, A.; Scarano, F.
Abstract: The Reynolds number effects on body limbs of a cyclist model, namely leg and arm, are investigated via robotic volumetric Particle Image Velocimetry measurements in the velocity range from 5 ​m/s to 25 ​m/s. The near wakes of such body limbs feature recirculation regions whose width and length are governed not only by the taper of the body parts, but also by the presence of coherent streamwise vortical structures. Moreover, the interaction with the wakes of the upstream body parts plays a role in the local wake properties. While reductions of the wake width are observed on both lower leg and arm with increasing free-stream velocity, the wake of the upper leg follows an opposite trend increasing in size at higher velocity. Such variations of wake width with the Reynolds number are related to the behaviour of the local drag coefficient, indicating a drag crisis behaviour on both leg and arm. The distribution of the so-called critical velocity upon these body segments is discussed, as it determines the freestream speed where a minimum value for the drag can occur. Highlights: Cyclist mannequin near-wake measured by robotic volumetric particle image velocimetry in a wide range of velocities. Reynolds number effects governed bycoherent streamwise vortical structures and wake interactions, in addition to limb taper. Variations of the local limb wake width with Reynolds number are related to the behaviour of the local drag coefficient. Distribution of the so-called critical velocity, corresponding to minimum drag coefficient, upon the body limbs is presented. Present findings serve as a reference for the design of low-drag skinsuits.